Dietary prevention of chronic obstructive pulmonary disease - Hirayama, F.; Lee, Andy (Nova Science Publishers, Inc., 2013)
Chronic obstructive pulmonary disease (COPD) is a lifestyle related chronic disease. Worldwide the prevalence of COPD is estimated to be about 10% in populations aged 40 years and over. The principal cause of COPD is cigarette smoking. While 95% of patients with COPD are smokers, 20% of smokers develop COPD. Therefore, other factors may mediate the development or offer protection against the disease. This study reviews the causes and treatment of COPD, and presents emerging evidence on dietary prevention from epidemiological studies. The risk of COPD may be reduced with an appropriate diet. In particular, increasing the consumption of vegetables and soy foods are associated with a decline in disease prevalence. The risk of COPD also appears to decrease with higher intake of green tea. However, the effects of fruit and fish consumption are inconsistent, whereas red meat intake is positively associated with the COPD risk. Further research is required to investigate the underlying mechanisms and to confirm the role of dietary factors for the prevention of COPD. © 2012 by Nova Science Publishers, Inc. All rights reserved.